Sosialisai Literasi Ekonomi Syariah Sejak Dini Pada Siswa Tahfidzul Qur’an Arrahmani - Restia Gustiana; Najikha Akhyati; Abdulloh Abdulloh (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2023)
This Community Service aims to socialize and provide an understanding of yariah economic literacy from an early age to Arrahmani Tahfidzul Qur'an students. Islamic economics is a system that requires the control of property to the public in accordance with the principles of justice. This is done to avoid hoarding excessive and stagnant assets so that they do not flow into the economy which results in reduced sectoral productivity which results in stalled economic acceleration. However, in practice there are still many people who do not understand the principles of Islamic economics. This is due to the lack or limited public knowledge of current Islamic economic literacy. For this reason, it is important to carry out socialization to increase literacy among Muslims, especially millennials. The method used in this service is to socialize face to face to students at the Tahfidzul Qur'an Arrahmani Foundation. The team from the UNPAM Islamic Economics Study Program successfully conducted socialization of Islamic economics to aliyah students of the Tahfidzul Qur'an Arrahmani Foundation.